2008
DOI: 10.1136/gut.2007.127878
|View full text |Cite
|
Sign up to set email alerts
|

Role of obesity in GORD-related disorders

Abstract: Obesity satisfies several criteria for a causal association with GORD and its complications including generally consistent association and some dose-response relationship. Abdominal obesity seems to explain a considerable part of this association operating mostly by increasing intragastric pressure, gastroesophageal gradient, TLOSR, and oesophageal acid exposure. Additional humoral mechanisms may be important in Barrett's oesophagus and oesophageal adenocarcinoma but this remains poorly examined. Maintaining n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(92 citation statements)
references
References 44 publications
4
83
0
5
Order By: Relevance
“…However, their exact pathogenetic role is still unclear, and the beneficial effect of specific recommended changes in lifestyle habits is controversial [10] . It is a common belief that some foods may induce or worsen GERD symptoms; in fact, in daily clinical practice, this leads to medical staff advising patients to avoid the suspected foods [47] .…”
Section: Dietary Habits In Patients With Gastroesophageal Refux Diseamentioning
confidence: 99%
See 2 more Smart Citations
“…However, their exact pathogenetic role is still unclear, and the beneficial effect of specific recommended changes in lifestyle habits is controversial [10] . It is a common belief that some foods may induce or worsen GERD symptoms; in fact, in daily clinical practice, this leads to medical staff advising patients to avoid the suspected foods [47] .…”
Section: Dietary Habits In Patients With Gastroesophageal Refux Diseamentioning
confidence: 99%
“…However, the most important reflux mechanism in obese subjects seems to be a transient lower esophageal sphi ncter relaxation [10] , generated by gastric distension, which leads to intense stimulation of both stretch and tension mechanoreceptors in the proximal stomach [4243] . Recently, a European study investigated the prevalence of central adiposity, metabolic syndrome, and a proin flammatory state in patients with Barrett's esophagus, and found that the proinflammatory impact of adipocytokines associated with the metabolic syndrome of central adi posity may play an important role in the pathogenesis of esophageal cancer [4445] .…”
Section: Role Of Metabolic Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Visceral adipose tissue is biologically active and can secrete pro‐inflammatory cytokines, especially IL‐6 and tumor necrosis factor‐α, which lead to insulin resistance 30. In addition, these cytokines may also be associated with a chronic inflammatory state in obesity, thus increasing the risk of erosive esophagitis 31. Nevertheless, it remains unclear what the underlying metabolic mechanisms are and whether other humoral factors are involved in the pathogenesis of obesity‐related erosive esophagitis.…”
Section: Discussionmentioning
confidence: 99%
“…After 10 and 20 years of follow-up, the NCCP-GI [30][31][32][33][34][35][36] The NCCP-GI group displayed less overall survival at all time points, specifically 70.1% at 10 years and 51.8% at 20 years, compared with their NCCP-U counterparts. The univariate analysis revealed an association between the NCCP-GI group and increased mortality (hazard ratio, 1.79; P=.007).…”
Section: Gi Testingmentioning
confidence: 99%